Sensitivity of Terminalia catappa L. Toward Aeromonas hydrophila - Purba, Andre Manusun; Riauwaty, Morina; Syawal, Henni (Jurnal Perikanan dan Kelautan, 2020)
Terminalia catappa is commonly present in tropical area  and its can be used for increasing pH in fish culture and it also be used as disinfectant.  A research aims to understand the dosages of T. catappa leaf extract to hamper the growth of Aeromonas hydrophila  has been conducted  from February  to July 2019.  A diffusion agar KIRBY BAUER method was applied to understand the sensitivity of T. catappa  toward the A. hydrophila. Treatments applied were P0 (Control, Oxytetracyclin (30 µg.Disk), P1 (100%), P2 (90%), P3 (80%), P4  (70%), P5 (60%), P6 (50%), P7 (40%), P8 (30%), P9 (20%), P10 (10%) P11 (9%), P12 (8%), P13  (7%), P14 (6%), P15 (5%), P16 (4%), P17 (3%), P18(2%), P19 (1%). Pure leaf extract was obtained from fresh leaf. The disk blank was wet with 50 L of leaf extract. A. hydrophila was cultured in TSA, TSB and GSP media, and it was grew up for 24 hours. Results shown that the pure leaf extract produce  13.9 mm diameter clear zone, while 2% of pure extract produce 6.5 mm diameter clear zone.